Tanshinone IIA alleviates ovalbumin-induced allergic rhinitis symptoms by inhibiting Th2 cytokine production and mast cell histamine release in mice - Qing Chen; Liping Shao; Yong Li; Mian Dai; He Liu; Nan Xiang; Hui Chen (Taylor & Francis Group, 2022)
Context Studies have shown that tanshinone IIA (TIIA) has an anti-inflammatory effect, but the effect on allergic rhinitis (AR) is unclear. Objective In this study, we explore the effect of TIIA on AR. Materials and methods AR mice model was established by the intraperitoneal (ip) injection of 50 μg ovalbumin (OVA). AR mice in the dose tested groups were treated with TIIA (10 mg/kg/d, ip) or dexamethasone (Dex) (2.5 mg/kg/d, oral). The number of nasal rubbing in mice was counted. Inflammatory, goblet and mast cells in nasal mucosal tissue were detected. The contents of histamine, OVA-immunoglobulin E (IgE), OVA-immunoglobulin G1 (IgG1), tumour necrosis factor-α (TNF-α), interleukin-4 (IL-4), IL-5, interferon-γ (IFN-γ) and IL-12 in nasal lavage fluid (NALF) or serum were measured. Human mast cells (HMC-1) were treated with C48/80 to release histamine or TIIA for therapeutic effect, and the cell viability, histamine content and mast cell degranulation were examined. Results OVA promoted the number of nasal rubbings in mice (78 times/10 min, p< 0.001), increased the inflammatory, goblet and mast cells in nasal mucosal tissue, and significantly (p< 0.001) elevated the levels of histamine (120 ng/mL), OVA-IgE (2 pg/mL), OVA-IgG1 (90 ng/mL), TNF-α (2.3 pg/mL), IL-4 (150 pg/mL) and IL-5 (65 pg/mL) in serum or NALF of OVA-induced AR mice. However, both TIIA and Dex inhibited the effect of OVA on AR mice. Besides, TIIA reversed the promotion of histamine release (30%) and mast cell degranulation induced by C48/80. Discussion and conclusions TIIA alleviates OVA-induced AR symptoms in AR mice, and may be applied as a therapeutic drug for patients with Th2-, or mast cell-allergic disorders.